HPV vaccination intention and its association with vaccine hesitancy and health beliefs among unvaccinated Chinese medical college students: A cross-sectional study - Ying-Ai Cui; Yuan Li; Liping Yang; Zheng-Ai Cui (PLoS ONE, 2026)
Background Human papillomavirus (HPV) infection poses a significant public health challenge, and HPV vaccination uptake among Chinese college students remains suboptimal. Therefore, it is essential to conduct ongoing, in-depth investigations into the psychological and cognitive mechanisms of HPV vaccination intention. This study aims to explore the associations among HPV vaccination intention, vaccine hesitancy, and health beliefs among Chinese medical college students. Methods A cross-sectional survey was conducted from June 16 to July 16, 2024, to assess sociodemographic characteristics, vaccine hesitancy, and health belief model (HBM) among college students at Guangdong Medical University. Descriptive statistics, univariate analysis, and binary logistic regression were performed to identify factors associated with HPV vaccination intentions among unvaccinated students. Results Among 3,584 unvaccinated participants, 73.16% expressed willingness to receive the HPV vaccine. The key significant associations identified included gender (male) (OR: 0.26; 95% CI: 0.22 ~ 0.31; p <  0.001), parental occupation (employees in enterprises, commercial, and service industries (including self-employed)) (OR: 1.43; 95% CI: 1.18 ~ 1.75; p <  0.001), and information sources (hospitals or doctors) (OR: 1.37; 95% CI: 1.15 ~ 1.64; p =  0.001). Vaccination intention was also directly associated with the perceived necessity (OR: 0.91; 95% CI: 0.88 ~ 0.94; p <  0.001) and importance (OR: 1.07; 95% CI: 1.03 ~ 1.10; p <  0.001) of vaccine hesitancy, as well as the perceived benefits of behavior for the HBM (OR: 1.21; 95% CI: 1.12 ~ 1.32; p <  0.001). Conclusions In this sample, Chinese medical college students demonstrated a relatively high willingness to receive HPV vaccination. Willingness was positively associated with perceived necessity, importance, and benefits of vaccination. Integrating structured clinician-delivered counseling into curricula, using parental occupation data for targeted subsidies, and embedding classroom sessions comparing personal HPV risk with vaccine safety data may improve uptake. Government evaluation of gender-neutral vaccination policies and provision of male-inclusive campus services are also recommended.